2003
DOI: 10.1017/s0032247403003206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of contamination by heavy metals and petroleum hydrocarbons at Atlas Cove Station, Heard Island

Abstract: Located on the northwest coast of Heard Island, a World Heritage-listed sub-Antarctic territory of Australia, Atlas Cove served as the site of the first permanently occupied Australian National Antarctic Research Expedition (ANARE) station (1947–55). Subsequent to its closure, Atlas Cove Station was abandoned and left largely to the mercy of the natural elements, although it has been visited and occupied on an infrequent basis by ANARE. All activities on the island are now subject to the provisions of the Hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 5 publications
0
21
0
3
Order By: Relevance
“…In instances where a shortage of research in the Antarctic and Arctic exists, recent research from temperate, alpine and lower latitude cold environments with relevance to the Antarctic and Arctic is considered and discussed. research stations (Snape et al 2001;Poland et al 2003;Stark et al 2003;Curtosi et al 2007). Snape et al (2001) identified petroleum-derived contamination as the most significant environmental pollution issue in the Antarctic.…”
Section: Introductionmentioning
confidence: 99%
“…In instances where a shortage of research in the Antarctic and Arctic exists, recent research from temperate, alpine and lower latitude cold environments with relevance to the Antarctic and Arctic is considered and discussed. research stations (Snape et al 2001;Poland et al 2003;Stark et al 2003;Curtosi et al 2007). Snape et al (2001) identified petroleum-derived contamination as the most significant environmental pollution issue in the Antarctic.…”
Section: Introductionmentioning
confidence: 99%
“…As amostras coletadas na Área 1 apresentaram maiores teores de HAs em relação às demais. O mesmo ocorreu no trabalho de Stark et al (2003) (Bícego et al 1996). No presente estudo, por se tratar de um estudo mais detalhado em toda área do entorno da EACF, as maiores concentrações foram encontradas próximo aos tanques de combustíveis.…”
Section: Discussionunclassified
“…Legacy waste tip and fuel spill sites around subantarctic and Antarctic research stations generally contain elevated concentrations of contaminants including metals [1][2][3]. Legacy waste tip and fuel spill sites around subantarctic and Antarctic research stations generally contain elevated concentrations of contaminants including metals [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It is common in wastewater discharges [22] and is found in legacy waste sites and fuel spills associated with polar research stations [1,3]. It is common in wastewater discharges [22] and is found in legacy waste sites and fuel spills associated with polar research stations [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation